'And since that time has never been heard of…' The forgotten boys of the sea: Marine Society merchant sea apprentices, 1772–1873. (2nd July 2020) - Withall, Caroline
ABSTRACT: The supply of child labour during Britain's industrial revolution conjures mental imagery of destitute children toiling in mines and mills, but in recent years, historians have demonstrated that children worked in many nooks and crannies of the economy, not just the highly visible new industries. The shipping industry was a vital component of Britain's commercial success in this period, yet the supply of boys has not received the same scrutiny as the children placed in the cotton industry. The Marine Society is best known for its pivotal role supplying the Royal Navy during manpower crises in the eighteenth century; this research highlights a lesser known aspect of its work, the recruitment of poor boys as apprentices to merchant ships. Using the Society's apprenticeship registers, information has been gathered on 25, 000 boys. Quantitative analysis is brought to life by contemporary newspaper reports and the Society's treasure trove of correspondence, in order to develop not only a missing piece of maritime history, but also consider themes with wider significance to social and economic history. Individual tales of tragedy and triumph reveal what life was truly like for the boys who rode the crest of the wave, offering an empathetic element to the research.